The role of endoscopy in the management of gastroesophageal reflux disease. Issue 1 (30th December 2021) - Kuribayashi, Shiko; Hosaka, Hiroko; Nakamura, Fumihiko; Nakata, Ko; Sato, Keigo; Itoi, Yuki; Hashimoto, Yu; Kasuga, Kengo; Tanaka, Hirohito; Uraoka, Toshio
Abstract: Gastroesophageal reflux disease (GERD) is a common disease that may cause a huge economic burden. Endoscopy is performed not only to rule out other organic diseases but also to diagnose reflux esophagitis or Barrett's esophagus. Non‐erosive GERD (non‐erosive reflux disease [NERD]) is called endoscopy‐negative GERD; however, GERD‐related findings could be obtained through histological assessment, image‐enhanced endoscopy, and new endoscopic modalities in patients with NERD. Moreover, endoscopy is useful to stratify the risk for the development of GERD. In addition, endoscopic treatments have been developed. These techniques could significantly improve patients' quality of life as well as symptoms.